Dangers in Business Management due to Discretion in the Application of Managerial Techniques in Processes of Change - Rosero Peña, Lucy (2016)
The main focus of this article is to investigate if there are potential dangers in business management due to the discretion in the application of managerial techniques in processes of change. We studied three private companies in order to compare the application of the techniques of changes based on the principles of Continuous Improvement and Total Quality, finding unwanted short and long term effects. The results support the application of a methodological process to successfully carry out processes of planned change, with a systemic approach, under a new concept of managerial technique, which, although does not rule out discretion, since it is a faculty of the management of organizations when making decisions, facilitates the choice of considerations and criteria for determining their specific characteristics and scope of action, in direct relation to the needs and objectives of change that are pursued. Finally, an explanatory model is proposed between the managerial techniques analyzed for the change process improvement and the need to integrate the application sequence in accordance with the required exchange rate, thus minimizing the negative impact in business management.